Perancangan Motion Comic Cerita Pewayangan Bima dan Dewa Ruci untuk Masalah Krisis Identitas pada Remaja - Ardiyansyah, Riyan; Kurniawan, Rahmat; Poerbaningtyas, Evy (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2024)
Adolescent identity crisis poses risks of leading youths toward negative behaviors such as depression, delinquency, and substance abuse. This design initiative aims to develop a motion comic as an educational tool for teenagers to navigate their self-identity. Employing Design Thinking, the process involves qualitative methods including 5W+1H analysis, interviews, literature review, document analysis, and online research. The motion comic,